A longitudinal study of post-haemorrhagic ventricular dilatation in the newborn. Issue 12 (December 1981) - Levene, M I; Starte, D R
Abstract : Two hundred and two consecutive admissions to a regional neonatal unit were scanned by real-time ultrasound. Sixty-eight (34%) infants had intracranial haemorrhage, 39 (57%) of whom were scanned repeatedly until they were at least 30 days old. Fifteen infants showed some degree of ventricular dilatation. Four had transient dilatation with complete recovery without any form of treatment (group 1), 7 showed persistent but non-progressive dilatation with no treatment (group 2), 3 had rapidly progressive hydrocephalus (group 3), and 1 had cerebral atrophy (group 4). Occipitofrontal head circumference was also followed sequentially from birth and was not abnormal in groups 1 and 2, but abnormal rates of head growth were seen in groups 3 and 4. It is concluded that after intracranial haemorrhage only a small proportion of infants develop frank hydrocephalus, but ventricular dilatation of some degree is common and may require no treatment.